Does Electrification Matter for Child Development? Evidence from Ethiopia. - Proffen, Celina (Journal of Development Studies, 2026)
This paper examines the impacts of a large-scale grid-electrification program in rural Ethiopia on child development using high-quality panel data on nearly 1,200 children and their families. I document a slow and limited take-up of electricity at the household-level: even five years after villages' connection to the grid, less than 50 per cent of village dwellings report having electricity access. Despite this finding, I observe important changes in children's daily routines, which point toward an important role of public infrastructure: upon electrification, children reduce their hours spent sleeping and helping their families by about 25 and 35 minutes, respectively. In addition, I document significant increases in the time that children spent on their education – both in and outside of school. Conditional on enrolment, these educational benefits are particularly pronounced for girls.